2017
DOI: 10.18865/ed.27.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Exercise in African Americans with High Levels of Inflammation

Abstract: Purpose: Systemic inflammation, measured by C-reactive protein (CRP), is an important risk factor for cardiovascular disease (CVD) and mortality. We investigated whether aerobic exercise training (AEXT) affects African Americans with high inflammation (HI) the same way it does African Americans with low inflammation (LI) in terms of CVD risk factors.Methods: 23 African Americans with CRP levels <3 mg/L (LI) and 14 African Americans with CRP ≥3 mg/L (HI) underwent six months of AEXT. Participants were sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Nevertheless, regular HPE was the most effective intervention in increasing both the aerobic capacity and the resistance to the risk of vascular thrombosis induced by hypoxia when compared to NPE [ 54 ]. Consistently, reduced levels of circulating activated EEVs were found following regular PE over six months in another trial [ 103 ]. The circulating EEVs may be uptaken by tissues engaged in crosstalk communication triggered by PE [ 62 ].…”
Section: Evidence Supporting the Triad Physical Exercise-extracellsupporting
confidence: 64%
“…Nevertheless, regular HPE was the most effective intervention in increasing both the aerobic capacity and the resistance to the risk of vascular thrombosis induced by hypoxia when compared to NPE [ 54 ]. Consistently, reduced levels of circulating activated EEVs were found following regular PE over six months in another trial [ 103 ]. The circulating EEVs may be uptaken by tissues engaged in crosstalk communication triggered by PE [ 62 ].…”
Section: Evidence Supporting the Triad Physical Exercise-extracellsupporting
confidence: 64%
“…There is limited research investigating the effects of exercise on EMPs, particularly in individuals with overweight/obesity. In one study, it was shown that six months of aerobic exercise training reduced CD62E+ EMPs by ∼38% and ∼59% in overweight/obese, sedentary and non‐diabetic African Americans with low or high levels of inflammation, respectively (Kretzschmar et al., 2017). Landsford et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research investigating the effects of exercise on EMPs, particularly in individuals with overweight/obesity. In one study, it was shown that six months of aerobic exercise training reduced CD62E+ EMPs by ∼38% and ∼59% in overweight/obese, sedentary and non-diabetic African Americans with low or high levels of inflammation, respectively (Kretzschmar et al, 2017). Landsford et al have shown that a short bout of continuous training increased CD62E+ EMPs up to 120 min post-exercise (with pronounced results in men but not women) compared to baseline levels (Lansford, 2016).…”
Section: Impact Of Exercise Training On Empsmentioning
confidence: 99%